BCG Infection after bladder cancer treatment – 3 clinical case reports - Alves, J (2015)
Immunotherapy with Bacillus Calmette-Guérin (BCG) to treat non-muscle invasive bladder cancer has become an effective and superior alternative to chemotherapy. Intravesical treatment with BCG appears to be relatively safe; however, occasionally BCG infection complicates such treatment. In the present work we describe three patients in whom BCG infection occurred after intravesical BCG therapy. All patients had positive urine culture forMycobacterium tuberculosis complex, using AccuProbe culture identification and then Genotype Mycobacterium MTBC test identified Mycobacterium bovis BCG. The diagnosis is difficult and microbiologic study is usually negative, so high index of suspicion is essential.